2010
DOI: 10.1007/s10620-010-1222-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Advantage of Highly Sensitive On-Chip Immunoassay for Fucosylated Fraction of Alpha-Fetoprotein in Patients with Hepatocellular Carcinoma

Abstract: μ-TAS AFP-L3 is more sensitive for discriminating HCC than the conventional LiBASys AFP-L3, particularly in subgroups with lower AFP concentrations and early-stage HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…4). Recent investigations have shown that diagnostic sensitivity of hs-AFP-L3% at a cut-off level of 5 or 7% was 41.5 or 41.1%, respectively, in HCC patients with serum AFP <20 ng/ml (18,22). Therefore, our findings in this study support the specificity of hs-AFP-L3% in patients with serum AFP <20 ng/ml, as previously reported.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…4). Recent investigations have shown that diagnostic sensitivity of hs-AFP-L3% at a cut-off level of 5 or 7% was 41.5 or 41.1%, respectively, in HCC patients with serum AFP <20 ng/ml (18,22). Therefore, our findings in this study support the specificity of hs-AFP-L3% in patients with serum AFP <20 ng/ml, as previously reported.…”
Section: Discussionsupporting
confidence: 90%
“…2). Since hs-AFP-L3% is reliable even when serum AFP is <20 ng/ml, it is possible to set the cut-off value for hs-AFP-L3% at 5-7% (18,22,23). We show here that at a cut-off level of 5%, the sensitivity and specificity of hs-AFP-L3% were 44.6 and 71.2%, respectively, in HCC patients with serum AFP <20 ng/ml (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, AFP-L3 has been recognized as a specific marker for HCC. Furthermore, analysis using this marker could be useful for monitoring treatment responses and disease recurrence and could also be a tool for recognition of HCC earlier than that possible by using imaging modalities (34,(37)(38)(39)(40)(41)(42). In recent years, in addition to AFP, new biomarkers possessing fucosides have been discovered.…”
Section: Discussionmentioning
confidence: 99%
“…However, an early increase in AFP levels correlates with poorer outcome with shorter OS and PFS [74] . Japanese groups proposed the lens culinaris agglutinin reactive AFP (AFP-L3), an isoform of AFP, as a good diagnostic and prognostic biomarker for HCC [75][76][77] . However, scant data is/are available regarding the value of AFP-L3 as predictive of response to antiangiogenic agents in HCC [78] .…”
Section: Poorer Prognosismentioning
confidence: 99%